2020
DOI: 10.1038/s41598-020-62773-7
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-Musculoskeletal Mapping for Man-Machine Interfacing

Abstract: We propose a myoelectric control method based on neural data regression and musculoskeletal modeling. this paradigm uses the timings of motor neuron discharges decoded by high-density surface electromyogram (HD-eMG) decomposition to estimate muscle excitations. the muscle excitations are then mapped into the kinematics of the wrist joint using forward dynamics. The offline tracking performance of the proposed method was superior to that of state-of-the-art myoelectric regression methods based on artificial neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 44 publications
0
49
0
Order By: Relevance
“…Interestingly, we found that by training the classifier on a small amount of participant-specific data, we achieved classification accuracy close to the ideal case of subject-specific training. In the context of neural interfacing, this finding implies that the extensive training periods usually required for an accurate calibration of HMIs [56], [57] can undergo significant reduction, shifting the paradigm towards more effective and user-friendly systems.…”
Section: Testing the Universality Of Peripheral Neural Informationmentioning
confidence: 99%
“…Interestingly, we found that by training the classifier on a small amount of participant-specific data, we achieved classification accuracy close to the ideal case of subject-specific training. In the context of neural interfacing, this finding implies that the extensive training periods usually required for an accurate calibration of HMIs [56], [57] can undergo significant reduction, shifting the paradigm towards more effective and user-friendly systems.…”
Section: Testing the Universality Of Peripheral Neural Informationmentioning
confidence: 99%
“…Recently proposed data models enabled identification of motor unit firings from HD-EMGs, recorded during repeated dynamic muscle contractions from healthy individuals [21], [124]. Moreover, work applied to amputees' residual muscles EMGs proved the possibility of decomposing motor unit action potential during concentric muscle contractions, predominant in transhumeral and transradial amputees' muscles in the residuum [19], [125].…”
Section: Discussionmentioning
confidence: 99%
“…Recent improvements in the measurement and real-time classification of myoelectric signals have already facilitated the use of sEMG in man-machine interfaces for controlling prostheses and orthoses among other devices (72)(73)(74)(75)(76).…”
Section: Application Of Semg In Controlling Hrc Technologiesmentioning
confidence: 99%
“…The performance of these man-machine interfaces is quickly improving owing to neuro-musculoskeletal models driven by neural information obtained from the decomposition of HDsEMG ( 72 ).…”
Section: An Overview Of Semg Use In Return-to-work Of Patients With Nmentioning
confidence: 99%
See 1 more Smart Citation